2022
DOI: 10.1002/anie.202201655
|View full text |Cite
|
Sign up to set email alerts
|

Electronically Engineering Water Resistance in Methane Combustion with an Atomically Dispersed Tungsten on PdO Catalyst

Abstract: Improving the low‐temperature water‐resistance of methane combustion catalysts is of importance for industrial applications and it is challenging. A stepwise strategy is presented for the preparation of atomically dispersed tungsten species at the catalytically active site (Pd nanoparticles). After an activation process, a Pd−O−W1‐like nanocompound is formed on the PdO surface with an atomic scale interface. The resulting supported catalyst has much better water resistance than the conventional catalysts for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 75 publications
1
40
0
Order By: Relevance
“…After deposition of Pd NPs, the surface Mn 3+ /Mn 4+ ratio rises from 1.33 (δ-MnO 2 -NFA) to 3.00 (0.05Pd/δ-MnO 2 -NFA), i.e., 0.05Pd/δ-MnO 2 -NFA owns more surface Mn 3+ than the δ-MnO 2 -NFA ( Table 3 ). Figure 7B illustrates the Pd 3d spectra of 0.05Pd/δ-MnO 2 -NFA and 0.05Pd-NP samples, which can be divided into four portions: the two at BE = 335.2 and 340.5 eV are belong to the surface Pd 0 species, while the other two at BE = 336.8 and 342.2 eV are due to the surface Pd 2+ species ( Xu et al, 2017 ; Dong et al, 2022 ; Hou et al, 2022 ). The surface Pd 2+ /Pd 0 ratio of 0.05Pd/δ-MnO 2 -NFA is 1.33, which is much higher than that of 0.05Pd-NP (0.15) ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…After deposition of Pd NPs, the surface Mn 3+ /Mn 4+ ratio rises from 1.33 (δ-MnO 2 -NFA) to 3.00 (0.05Pd/δ-MnO 2 -NFA), i.e., 0.05Pd/δ-MnO 2 -NFA owns more surface Mn 3+ than the δ-MnO 2 -NFA ( Table 3 ). Figure 7B illustrates the Pd 3d spectra of 0.05Pd/δ-MnO 2 -NFA and 0.05Pd-NP samples, which can be divided into four portions: the two at BE = 335.2 and 340.5 eV are belong to the surface Pd 0 species, while the other two at BE = 336.8 and 342.2 eV are due to the surface Pd 2+ species ( Xu et al, 2017 ; Dong et al, 2022 ; Hou et al, 2022 ). The surface Pd 2+ /Pd 0 ratio of 0.05Pd/δ-MnO 2 -NFA is 1.33, which is much higher than that of 0.05Pd-NP (0.15) ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The addition of Fe, Co, and Sn on Pd/TiO 2 could enhance the stability of the catalyst, whereas Ni and Zn additives could enhance the activity and stability of the catalyst. 68 Recently, Hou et al 69 proposed the synthesis of PdW 1 /Al 2 O 3 via dispersing atomic W species on PdO particles. Pd exhibited similar activity and much higher resistance to water compared to Pd/Al 2 O 3 .…”
Section: Mixed Mechanismmentioning
confidence: 99%
“…Several attempts had been made to enhance the water resistance, including modification of catalyst components and structures, addition of water adsorbent, and so on. Various bimetallic catalysts exhibited higher stability than Pd catalysts in the presence of water vapor and showed stability after a long process of mild aging treatment. ,,, Some special structures showed superior water-resistant ability, including Pd-NiCo 2 O 4 catalyst with Pd inserted into the NiCo 2 O 4 lattice, Pt-Pd/CeO 2 bimetallic catalyst prepared by ball-milling with mushroom-like structure of Pt-Pd phase in the aged catalyst, and Pd catalysts encapsuled in a core–shell structure. , Addition of extra water adsorbent was also a method to enhance water resistance. Huang et al discovered that the dilution of Pd/CeO 2 with CaO caused a 5-fold increase in activity compared to Pd/CeO 2 catalysts, and the enhancement could last for over 10 h on stream.…”
Section: Atmospherementioning
confidence: 99%
“…The one is that CH 4 can be converted into CO 2 very fast at 300-400 °C, owing to the sufficient supply of oxygen species with high oxidative potential. [16] The other one is that CH 4 was electro-catalytically converted to CH 3 OH even at much lower temperature of only 100 °C, as the desirable oxygen species were generated from gaseous O 2 at low temperature. [17] Cyclic voltammetry experiments indicated that the generation of such active oxygen species was strongly dependent on the VO x surface structure.…”
Section: Reaction Mechanism and O 2 Activationmentioning
confidence: 99%
“…However, we are suspicious about this attribution to the OCM light‐off at so high temperature based on the following facts. The one is that CH 4 can be converted into CO 2 very fast at 300–400 °C, owing to the sufficient supply of oxygen species with high oxidative potential [16] . The other one is that CH 4 was electro‐catalytically converted to CH 3 OH even at much lower temperature of only 100 °C, as the desirable oxygen species were generated from gaseous O 2 at low temperature [17] .…”
Section: Introductionmentioning
confidence: 99%